Detection of Bartonella vinsonii, Anaplasma platys and Bartonella sp. in didelphis marsupialis, Pecari tajacu and Chelonoidis denticulate: Peru - Rojas-Jaimes, Jesús (2023)
Introduction: Evidence suggest that wildlife Infectious diseases related to wildlife are of most importance because of the agents’ capacity to spill over into humans from the wild reservoir. Among them, the bacteria Bartonella spp. and Anaplasma spp. are related to this zoonotic dynamic. Objective: The primary goal of the present study was to determine the presence of pathogenic bacteria in kidney and liver tissues of Didelphis marsupialis; spleen, liver, and skin of Pecari tajacu; spleen, liver, and skin of Chelonoidis denticulata. Methodology: A PCR using universal and specific primers for 16 S rRNA, of Bartonella spp. with subsequent genetic sequencing were used. Results: The results in this study indicate that Bartonella vinsonni was detected in the liver tissue of Didelphis marsupialis using both universal primers and those specific for Bartonella sp. Anaplasma platys was detected at the liver and spleen level using universal primers. Additionally, Bartonella spp. was found at the liver, spleen, and skin level in Pecari tajacu using the specific primers. Finally, using the universal and specific primers at the skin level, Bartonella spp. was evident in Chelonoidis denticulata. Conclusions: The presence of the DNA of the Bartonella vinsonii was detected at the liver tissue in Didelphis marsupialis. DNA of the Anaplasma platys and Bartonella spp. were identified at the spleen and liver level. This study also identified that DNA Bartonella spp. was detected in Pecari tajacu skin. Finally DNA of Bartonella spp. was evident in Chelonoidis denticulate skin. The findings of this study suggest that these bacteria are present in these animals and may be responsible for outbreaks.